KISAH LUKMAN AL-HAKIM DALAM AL-QURAN SEBAGAI PRIMADONA PENDIDIKAN KELUARGA BERBASIS KESETARAAN GENDER MENURUT PERSPEKTIF PENDIDIKAN ISLAM - K, ABDULLAH (PSW, 2012)
Story of Lukman al-Hakim presented by Allah swt. As a best figure because his kindliness. In the holy Qurâan is mentioned directly in surah Lukman (31) verse 12-19 in order to become guidance that will confirm the moslemâs belief and can take a good lesson, that known in islam as hikmah, ibrah and mauidah in that story. It is a signal an guide from Allah in order to be and aplecated by all parents in their family without differences between boy and daughter. Also as Lukman al-Hakim can be taken as a model in education of Islam.